The role of therapeutic education in patients with diabetes - Bernas, Małgorzata; Szczeklik-Kumala, Zofia (Przewodnik Lekarza/Guide for GPs, 2009)
Diabetes mellitus is a chronic disease. Therapeutic education belongs to the most important part of treatment. The patients and therapeutic team ought to collaborate. There are different forms of therapeutic education – individual, group and through the mass media. There are therapeutic standards which improve the quality of a diabetic’s life.